Progress and problems in bacterial systematics - LESSEL, ERWIN F. (International Journal of Systematic and Evolutionary Microbiology, 1970)
ABSTRACT Considerable progress has been made in bacterial systematics, particularly in characterization and in approaches to determining the relationships of bacteria. Nonetheless real progress is difficult because much of the older literature is inadequate in terms of the present state of knowledge and because original strains do not exist wherewith sense can be made out of the older literature. It is felt that bacterial systematics could be placed on a firm foundation the following steps were taken: 1) revise the Bacteriological Code so that in order for a name to be validly published a prescribed minimal description would be required as would deposition of the type strain in a culture collection from which it would be available; 2) establish a date in the future as the starting date for names of bacteria, conserving, however, those names of recognizable taxa for which there are adequate descriptions and type strains (if the organism is cultivable), and 3) where indicated, acquaint authors and editors with the requirements for valid publication and with sound taxonomic practices.